Specific detection of latent human blood fingerprints using antibody modified NaYF4: Yb, Er, Gd fluorescent upconversion nanorods. (February 2018) - Liu, Cui-Mei; Zhang, Ling-Yu; Li, Lu; Li, Bai-Yu; Wang, Chun-Gang; Wang, Ting-Ting
Abstract: Blood fingerprints are an important subclass of fingerprint evidence when processing a violent crime scene. The commonly used method by the perpetrators to conceal blood stain is rinsed with water or mixed with the blood of livestock or poultry. The aim of the research presented was to overcome the above drawbacks. Herein, NaYF4 : Yb, Er, Gd fluorescent upconversion nanorods were conjugated with anti-hHb (UCNRs/anti-hHb) through a coupling reaction. We then used the resultant UCNRs/anti-hHb to detect the fingerprints that inked with the blood of human, porcine and chicken. The latent human blood fingerprints showed improved contrast, whereas the blood fingerprints of porcine and chicken did not. The consequence of detection exhibited that UCNRs/anti-hHb offered the ability of specific recognition. To assess the suitability of the UCNRs/anti-hHb for potential operational use, a variety of parameters (e.g., blood concentration, substrate types and aged time) were investigated. The effectiveness of UCNRs/anti-hHb was also assessed in comparison with Acid Yellow 7 (AY7, an effective blood reagent). The results demonstrated that UCNRs/anti-hHb provided high specificity, high sensitivity, good applicability, and low background, enabling practical applications in forensic sciences. Graphical abstract: Anti-hHb functionalized NaYF4 : Yb, Er, Gd fluorescent upconversion nanorods were used to specifically recognize latent human blood fingerprints on various surfaces, simultaneously inhibiting enhancement of blood marks of livestock and poultry. The specific recognition exhibited high specificity, high sensitivity, good applicability, and low background. Highlights: Anti-hHb functionalized upconversion nanorods are used for human blood fingerprints recognition. They show high specificity, high sensitivity, good applicability, and low background. They are superior to Acid Yellow 7 (a blood-sensitive reagent) on all substrates.